2003
DOI: 10.1002/mabi.200350026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chitin/Chitosan and Their Oligomers/Monomers on Migrations of Macrophages

Abstract: The effects of chitin/chitosan and their oligomers/monomers on the migrations of mouse peritoneal macrophage (PEM) and the rat macrophage cell line (rMp) were evaluated in vitro. In direct migratory assay using the blind well chamber method, the migratory activity of PEM was enhanced significantly by chitin and chitosan oligomers (NACOS and COS, respectively), but reduced by chitin, chitosan, and the chitosan monomer (GlcN). The migratory activity of rMp was increased significantly by chitin, chitosan, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 18 publications
5
22
0
Order By: Relevance
“…Secretion of TNF-α, produced mainly by activated macrophages, provides a convenient marker of macrophage activation (Yu et al, 1990). Our studies showed that both phagocytosis ability and TNF-α production of macrophages were significantly enhanced by carboxymethyl-chitosan, which were consistent with the study of Okamoto (Okamoto et al, 2003a), who reported that migration activity of macrophage was enhanced by chitosan. The interaction between chitosan and macrophages is generally attributed to mannose receptors in macrophages.…”
Section: Discussionsupporting
confidence: 92%
“…Secretion of TNF-α, produced mainly by activated macrophages, provides a convenient marker of macrophage activation (Yu et al, 1990). Our studies showed that both phagocytosis ability and TNF-α production of macrophages were significantly enhanced by carboxymethyl-chitosan, which were consistent with the study of Okamoto (Okamoto et al, 2003a), who reported that migration activity of macrophage was enhanced by chitosan. The interaction between chitosan and macrophages is generally attributed to mannose receptors in macrophages.…”
Section: Discussionsupporting
confidence: 92%
“…Chitosan oligosaccharides have a stimulatory effect on macrophages, and both chitosan and chitin are chemo-attractants for neutrophils in vitro and in vivo (Chen, Wang, Liu, & Wang, 2008). Chitin oligomers and chitosan oligomers, generated by enzymatic degradation in a wound environment, exert significant biochemical effects, as studies have shown the migratory activity of mouse peritoneal macrophages are significantly enhanced (Moon et al, 2007;Mori et al, 2005;Okamoto et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Conversely, chitosan oligosaccharide (COS), the soluble degradation product of chitosan, has a low molecular weight, good solubility and low viscosity and, furthermore, may be absorbed more readily by animals and humans than chitosan (Muanprasat and Chatsudthipong 2017). Studies have shown that COS possesses multiple functional properties, including anti-oxidation (Fernandes et al 2010), anti-inflammation (Lee et al 2009) and immune-enhancing characteristics (Okamoto et al 2003). Researches have also revealed that COS can be used as a substitute to antibiotics and confer marked health benefits in animals (Yang et al 2012;Xie et al 2015;Suthongsa et al 2017).…”
Section: Introductionmentioning
confidence: 99%